Evaluating task shifting to the clinical technologist in Dutch healthcare: A mixed methods study. - Maarten de Haan; Yvonne van Eijk-Hustings; Monique Bessems-Beks; Daisy De Bruijn-Geraets; Carmen Dirksen; Hubertus Vrijhoef (PLoS ONE)
Background Expected rise in the demand for healthcare and a dropping supply of healthcare professionals, has generated an increased interest in the most effective deployment of healthcare professionals. Consequently, task shifting has become a common strategy to redistribute tasks between established professional groups, however, little is known about the effects of shifting tasks to emerging professional groups. The aim of this study was to evaluate a legal amendment to facilitate task shifting to an emerging profession in Dutch healthcare: Clinical Technologists (CTs). CTs were introduced and provided an Extended Scope of Practice (ESP) to perform nine 'reserved procedures' independently. Methods A concurrent multi-phase mixed methods study was used to evaluate whether a legal amendment to facilitate task shifting to CTs was effective and efficient. Results The results show that CTs use their ESP frequently to perform five categories of reserved procedures independently and suggest that the ESP increased the efficiency of care delivery for those procedures. Additionally, the findings highlight that task shifting was influenced by the setting in which CTs worked, time allotted to patient-contact as well as external factors (e.g., financing). Conclusions This study provides tentative lessons for policymakers on how task shifting to emerging professional groups can be improved. Providing a legal amendment to facilitate task shifting to CTs seems to be effective and efficient. However, it also poses multiple challenges. While established professional groups can face similar challenges, it is likely that these are exacerbated for emerging professional groups, particularly when shifting tasks occurs horizontally.